MODEL OPTIMALISASI INTEGRASI PENDIDIKAN EKONOMI SYARIAH PADA PONDOK PESANTREN DI MADURA - Ryval Ababil; Ridan Muhtadi; Ririn Tri Ratnasari (LP2M IAI Miftahul Ulum Pamekasan, 2017)
Islamic economic education in Indonesia is very important. Especially if you look at the growth of the financial industry and Islamic business which is quite rapid. So it was felt that there was a need for efforts to instill the divine economics in the younger generation, namely in the period before college. The concept of integrating Sharia economic education with extracurricular systematic student cooperatives is a sufficiently accurate strategy to create young generations of Muslim candidates for practitioners and academics who understand sharia economics.